Additive‐Assisted Crystallization Dynamics in Two‐Step Fabrication of Perovskite Solar Cells. Issue 12 (20th October 2017) - Abzieher, Tobias; Mathies, Florian; Hetterich, Michael; Welle, Alexander; Gerthsen, Dagmar; Lemmer, Uli; Paetzold, Ulrich W.; Powalla, Michael
Abstract : Perovskite absorber layers for thin‐film solar cells can be fabricated by a variety of methods including solution‐ and vacuum‐based methods. Solution‐processed perovskite thin‐films prepared by two‐step methods often suffer from small grains and thus reduced optoelectronic performance. In this work, a simple and universal way to control the crystallization dynamics of perovskite (CH3 NH3 PbI3 ) layers prepared by thermal evaporation of lead iodide and a subsequent solution‐based conversion in methylammonium iodide solution is presented. By adding small concentrations of the non‐toxic additive hypophosphorous acid (HPA) in the second fabrication step, a facile way to maintain improved morphology and high quality perovskite films with large crystal size and low number of pin‐holes is demonstrated. Therefore, this approach provides an additional handle to influence the structural properties of perovskite films. In this study, the improved morphology results in an overall increase in power conversion efficiency from 5.1% to 8.0%. The additive‐assisted control of crystallization dynamics in perovskite layers is shown to be suitable both for small area deposition techniques, like spin‐coating, as well as large scale deposition techniques, such as inkjet printing. Moreover, it is validated that the additive improves the crystallization on a large variety of substrate materials as well as in ambient and inert process environments. Abstract : Deposition techniques for perovskite solar cell absorbers are numerous, however, in most cases they are highly specialized in terms of absorber composition and process environment . Here, a novel deposition technique based on thermal evaporation of lead iodide layers followed by a solution‐based conversion into perovskite is reported. To achieve high‐quality absorber layers a small amount of non‐toxic hypophosphorous acid is added in the second step, which is shown to be a facile and cheap way to control the morphology of the absorber in a variety of different process conditions.